Change in body composition in patients with achalasia before and after peroral endoscopic myotomy. Issue 4 (24th November 2019) - Mizusawa, Takeshi; Sato, Hiroki; Kamimura, Kenya; Hashimoto, Satoru; Mizuno, Ken‐ichi; Kamimura, Hiroteru; Ikarashi, Satoshi; Hayashi, Kazunao; Takamura, Masaaki; Yokoyama, Junji; Terai, Shuji
Abstract: Background and Aim: Patients with achalasia experience weight loss because of dysphagia caused by impaired relaxation of the lower esophageal sphincter. This study aimed to use dual bioelectrical impedance analysis (BIA) to determine the change in bodyweight and body composition in patients with achalasia before and after peroral endoscopic myotomy (POEM). Methods: Patients with achalasia who underwent POEM from 2013 to 2018 ( n = 72) were retrospectively analyzed for change in bodyweight before and after 3 months. Additionally, change in body composition was prospectively investigated in the final 10 of 72 patients using non‐radiation dual BIA. Results: Twenty patients (27.8%) were underweight (body mass index < 18.5) before undergoing POEM. No clinical parameters were identified to be associated with the underweight condition before POEM and be predictive of an increase in bodyweight after POEM. Low visceral fat volume observed on dual BIA correlated closely with the result obtained using computed tomography (Pearson correlation coefficient: r = 0.850, P < 0.01). Patients with achalasia had a statistically significant increase in visceral ( P < 0.01) and subcutaneous fat volumes ( P < 0.01) after POEM. Skeletal muscle mass index slightly increased ( P = 0.02), although the value after POEM was still low. No blood biomarkers were indicators for low bodyweight or low visceral fat volume. Conclusions: Dual BIA is an effective non‐invasive tool to evaluate the change in body composition of underweight patients with achalasia. Skeletal muscle volume was not enough after POEM, although a rapid increase in the intra‐abdominal fat volume was observed. Additional studies are warranted to understand the pathological implications.